Modelo e sugestão de zonas para implantação de Pontos de Entrega Voluntária (PEV) de Resíduos da Construção Civil (RCC) em Campo Mourão-PR - Xavier, Lucas Machado (2021)
The constant increase in urbanization brings several benefits such as housing, basic sanitation, quality of life, among others. However, the accelerated and unstructured growth affects the local effects that compromise the well-being of the individual, affecting mainly the environment where he is inserted, be it general or individual. Thus, the large number of new constructions, highways, renovations and demolitions, brings with it an increase in the generation of waste from civil construction and, linked to this, the need for the correct and sustainable destination for such. The Municipality of Campo Mourão-PR, approved Lei 4174/2020 on the Municipal Plan for the Management of Civil Construction Waste and begins to make progress in the management of such waste, however the destination and collection of small generators is still an unachieved objective. , for not having appropriate and regularized places to receive them. Therefore, the objective of the present work was to define an adequate model, through the analysis of Voluntary Delivery Points (VPD) in the city of Parana State and adequate according to models present in the literature, and zones for the implantation of VPD in the Municipality by through an analysis of the urban fabric by geographic information system. Two more viable proposals were obtained, a) 1 VDP of 3200m² installed in one of the areas with an area of influence of 7 kilometers and b) 2 VDP of 1600m² installed in the areas located in the southwest and northwest regions from Campo Mourão-PR. Such proposals must be analyzed and chosen by the Public Power. Therefore, such proposals subsidized the decision makers of the Public Management in relation to the definition of the model and the area of installation of VDP, thus contributing to the attendance of the small generator and, consequently, the reduction of environmental impacts caused by the irregular dispositions.